Converter based distributed drive system with enhanced dynamic response. (2021) - Gnana Saravanan, A.; Arul Jose, R.; Ebby Darney, P.; Sabarish, P.
Abstract: In this paper optimized converter based motor drive system is presented with enhanced dynamic response. A detailed design including source, storage and motor drive is proposed for various operating modes. The controlled distribution system is experimented to meet a guideline of the industry specific applications. Furthermore, compensation is provided from the power regenerated inside the drive. The storage with cascaded converters can supply the additional energy requirements when the drive is subjected to transients. The optimized controller is designed to control the individual phase voltage, speed and the firing angle of cascaded and lead converter. A voltage balancing control with isolated power regenerative control system is established to achieve the smooth power flow in the designed drive system. The experimental output voltage, Power flow and speed control are presented to explain the systems dynamic performance.